Glukhoye Lake: Middle to Late Holocene environments of Kunashir Island (Kuril Archipelago, Russian Far East). (27th October 2021) - Lozhkin, Anatoly V.; Cherepanova, Marina V.; Anderson, Patricia M.; Minyuk, Pavel S.; Finney, Bruce P.
Abstract : A multiproxy analysis of a sediment core from Glukhoye Lake in the southern Kuril Islands indicates that the basin originated c . 8.2 cal. ka BP as a brackish lagoon with the subsequent development of a freshwater lake ( c . 4.0 to 3.3 cal. ka BP), a bog ( c . 3.3 to 2.4 cal. ka BP) and a second lake ( c . 2.4 cal. ka BP to present). The basin history primarily reflects local coastal dynamics and is not related to proposed Archipelago‐wide changes in sea level. Between c . 8.2 and 8.0 cal. ka BP, the vegetation of southern Kunashir Island was characterized by Betula–Quercus forest with a secondary component of temperate broadleaf trees. Quercus broadleaf forest established c . 8.0 to 6.5 cal. ka BP and represents the Holocene thermal maximum. The remainder of the record shows a gradual decrease in temperate and an increase in conifer taxa, indicating a gradual cooling from the Holocene thermal maximum to c . 2.3 cal. ka BP. Maxima in Picea and Abies pollen between c . 2.3 and 1.1 cal. ka BP suggest conditions that were slightly cooler than present. Palaeovegetation changes in the Kuril Islands as inferred from lake and section data differ in the timing and/or composition of the vegetation communities, although results from the two types of sites become more similar as the number of sections increases. The lake results do not support a previous conceptual model developed for the southern Russian Far East, which linked changes in sea levels to Holocene climate fluctuations. Rather the depositional environments in the lake cores seem more related to coastal dynamics that are independent of fluctuations in sea levels or climate. The difficulty in developing accurate age models for sites with multiple depositional environments may be the most important obstacle for documenting and understanding the Archipelago's vegetation and climate histories. Abstract : A c. 8.2 cal. ka BP multiproxy lake record from the southern Kuril Islands indicates the occurrence of the Holocene thermal maximum between c. 8.0 to 6.5 cal. ka BP, followed by a gradual cooling to modern at c. 2.3 cal. ka BP. These results when combined with other lacustrine sites in the archipelago do not support previous conclusions that had linked Holocene climate change to sea level fluctuations.